Analysis of Trends and Management of Leprosy in Padang City - Rosmi; Salma; Vivit Novianti; Syahwa Ramadhani; Samal (Journal of Epidemiology and Health Science, 2025)
Background: Leprosy is a chronic granulomatous disease that primarily affects the skin and peripheral nerves and is caused by Mycobacterium leprae. Despite being one of the oldest known infectious diseases, leprosy remains associated with strong social stigma and discrimination. These social barriers often delay treatment-seeking behavior and contribute to adverse clinical and psychosocial consequences for affected individuals. Objective: This study aimed to describe the number of leprosy cases in Padang City from 2017 to 2021, to outline the clinical manifestations and management of leprosy, and to highlight prevention and control efforts implemented at the primary health care level. Methods: Secondary data were obtained from the Padang City Health Profile for the period 2017–2021, an annual report published by the Padang City Health Office. Data were collected through the recording and reporting system of community health centers (Puskesmas) in Padang City. Descriptive analysis was conducted based on the number of cases, age distribution, sex, and trends in new case detection. Results: In 2021, a total of 19 new leprosy cases were reported in Padang City. The leprosy prevalence rate was 0.47 per 10,000 population, while the proportion of new cases with grade 2 disability reached 10.52%, indicating delays in early detection. Case finding was primarily conducted through active screening activities and home visits by health workers. Conclusion: Although the prevalence of leprosy in Padang City remains relatively low, the continued detection of new cases indicates that leprosy has not yet been fully eliminated. Strengthening early detection, ensuring comprehensive treatment, and reducing social stigma are critical strategies for interrupting leprosy transmission and improving patient outcomes in the community.